First isolation and full-length genome analysis of a new RNA virus, Wenzhou sobemo-like virus 4 from Culex tritaeniorhynchus - Yuli Zhang; Yu Bi; Xiaohui Zou; Zhen Wu; Hengyi Sun; Jian Song; Guoyu Niu (Virulence, 2025)
Arboviruses are a major public health concern. Wenzhou sobemo-like virus 4 (WZSLV4) is a recently identified single-stranded RNA mosquito-borne virus. In this study, 3608 mosquitoes were collected from Shandong Province, China, and divided into 58 pools according to species and sex. qRT-PCR and nested PCR were used to confirm the presence of WZSLV4. Cell culture was used to isolate the virus, and the growth characteristics of WZSLV4 were observed. WZSLV4 was detected in Aedes albopictus (12.07 %, 7/58) and Culex tritaeniorhynchus (18.97 %,11/58). WZSLV4 replicated effectively in C6/36 cells but grew slowly in Vero and BHK cells without causing cytopathic effect (CPE). Phylogenetic analysis demonstrated that WZSLV4 was closely related to the Guangzhou sobemo-like virus and Sichuan mosquito sobemo-like virus, which belongs to the family Solemoviridae. Pairwise distance analysis indicated that 11 partially amplified sequences shared a high nucleotide identity. The objective of this study was to isolate and characterize WZSLV4 from mosquito populations in Shandong Province, China, and to evaluate its growth characteristics in different cell lines to better understand its biological properties and potential pathogenicity. To our knowledge, this is the first report on the isolation of WZSLV4 from mosquitoes, along with a description of the biogenic characterization of WZSLV4 in different cell lines. Nevertheless, further studies are needed to assess the potential pathogenic risks in mammals and humans.